The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/20009666.2018.1470441
|View full text |Cite
|
Sign up to set email alerts
|

A case of recurrent obscure gastrointestinal bleeding: Heyde’s syndrome – case report and review

Abstract: Gastrointestinal bleeding from angiodysplasias in patients with aortic stenosis is termed as ‘Heyde’s syndrome’. We report a case of Heyde’s syndrome successfully treated with trans-catheter aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
(16 reference statements)
0
11
1
Order By: Relevance
“…For patients who are not surgical candidates or those with numerous comorbidities placing them at a high risk for surgical intervention, TAVR is always preferred. 9 Additionally, for patients who decline TAVR or those who are not candidates for valve replacement, medical management becomes the primary treatment approach. 8 It consists of oral iron supplementation and/or regular blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who are not surgical candidates or those with numerous comorbidities placing them at a high risk for surgical intervention, TAVR is always preferred. 9 Additionally, for patients who decline TAVR or those who are not candidates for valve replacement, medical management becomes the primary treatment approach. 8 It consists of oral iron supplementation and/or regular blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the mechanical shear stress on the HMW vWF multimers inhibiting their cleavage by ADAMTS13 and consequently improves coagulation abnormalities implicated in Heyde's syndrome. There are several observational studies that have demonstrated potential therapeutic benefits of AVR [45][46][47][48][49][50][51][52][53]. All studies were published between 2010 and 2020; cessation of gastrointestinal bleeding following AVR was the most measured outcome.…”
Section: Aortic Valve Replacementmentioning
confidence: 99%
“…Subsequently, the patient underwent a balloon valvuloplasty for his severe symptomatic AS. He was not deemed to be a candidate for surgical aortic valve replacement (AVR) given his social status of being homeless and was also 1 1 Upon discharge, the patient was admitted again multiple times with recurrent melena, dizziness, and acute blood loss anemia requiring blood transfusions. An EGD with push enteroscopy was repeated twice, which showed multiple duodenal and jejunal angiodysplastic lesions (Figure 2), which were treated with argon plasma coagulation.…”
Section: Case Presentationmentioning
confidence: 99%
“…The coexistence of aortic valve stenosis (AS) and recurrent gastrointestinal (GI) bleeding from intestinal angiodysplasia (IA) is known as Heyde's syndrome [1,2]. This association was first described by Edward Heyde, MD, in 1958, when he reported 10 elderly patient cases with concurrent AS and GI bleeding [3].…”
Section: Introductionmentioning
confidence: 99%